Influence of drought stress on interactions of cotton (Gossypium hirsutum), twospotted spider mites (Tetranychus urticae), and western flower thrips (Frankliniella occidentalis) - Krauska, John Joseph Jr. (Kansas State University, 2019)
Drought is a concern for crop production in the High Plains region of the United States which is predicted by climate models to become exacerbated by regional climatic changes and high-output irrigation that is diminishing the finite underground water resources of the Ogallala Aquifer. In addition to drought conditions, changes in pest pressure due to indirect effects of drought stress also occur. The western flower thrips (Frankliniella occidentalis) is known as an economically important early-season pest insect pest of cotton and it also preys on the eggs of the herbivorous twospotted spider mite (Tetranychus urticae). It is unknown how the relationship between these two arthropod species could be altered during drought conditions in an agricultural setting. Chapter 1 discusses the interplay of these issues and states that the overall goal of the thesis was to examine the net effect of drought on plant-arthropod interactions. Chapter 2 examined the three-way responses of the plant and two arthropods to drought stress in a controlled greenhouse environment over a two week period. Drought conditions directly reduced spider mite populations, plant development, and stomatal gas exchange. Also, drought had indirect negative effects on plant development and physiological functions from the pestiferous activity of the arthropod populations. We infer that these plant responses reduced the seedling’s quality as a host plant which resulted in the observed reductions in spider mite populations when thrips were absent as well as when they were present. The net effect of drought on seedling cotton was compounded by the arthropod dynamics, despite any predation thrips may have enacted on the mite egg populations. Chapter 3 examined the question: do thrips adjust their omnivorous feeding behavior under drought conditions? We approached this question with a 72-hour experiment in which we recorded the amount of herbivorous and predacious feeding by thrips under well-watered and drought conditions. Thrips consumed more mite eggs under drought conditions while the amount of thrips feeding scars on the plant remained the same. We suspect that thrips are supplementing their diet with mite eggs because of reduced plant quality and potential plant defense hormones. Chapter 4 expands on how the results from these two experiments support our conclusion that the net effect of drought stress is largely negative for early-season cotton seedlings. Application of the findings from this thesis can assist with present-day pest and crop management in areas such as proper pesticide utilization and water conservation, which will prepare crop producers for future climatic conditions.
Keywords: Thrips; Spider mites; Drought; High Plains; Cotton; Agriculture